Density Figure of Aedes aegypti Larvae in the Laboratory Center of Universitas Nasional and Its Surrounding Residences - Nico Hartandi; Hasni Ruslan; Tatang Mitra Setia (Journal of Tropical Biodiversity, 2026)
Dengue remains a public health problem in Indonesia, caused by dengue virus with Aedes aegypti as the primary vector. Vector control requires data on larval density as an indicator of transmission risk. This study aimed to calculate the larval density of Ae. aegypti at the Laboratory Center of Universitas Nasional (UNAS) and its surrounding residences, and to describe the location and types of water-holding containers that potentially serve as mosquito breeding sites. The study was conducted from May to August 2025 using a descriptive observational approach. A total of 100 houses (premises) and 287 water-holding containers were inspected to calculate the House Index (HI), Container Index (CI), Breteau Index (BI), Density Figure (DF), and Larvae-Free Index (ABJ). The results showed HI = 38%, CI = 21%, BI = 59, DF = 6, and ABJ = 62%, indicating high larval density and a potential risk of dengue transmission. Most positive water-holding containers were found outdoors, and the most common container type identified was bucket. These findings suggest that environmental conditions still support mosquito breeding. It is recommended that the community routinely implement mosquito breeding site eradication activities based on the 3M-Plus principle (Menguras: draining and scrubbing containers; Menutup: tightly covering containers; Mendaur ulang: reusing or recycling discarded items; plus: additional preventive measures), that larval monitoring cadres (JUMANTIK) expand the coverage of larval surveillance, and that future research broaden its scope and methodology to obtain a more comprehensive understanding